Asymptotic behavior and numerical simulation by finite difference for the vibration model of a standard linear solid with thermal effect - Romero Figueroa, Carlos Javier (2021)
In this work, applying the semigroup theory of linear operators, we study the asymptotic behavior of the solutions of a coupled system that models the vibrations of a standard linear solid with a dissipative thermal effect. In order to verify numerically the established analytical results, a series of numerical simulations are carried out in their one-dimensional form, for which we consider the numerical scheme applying finite differences.